Psychometric Properties and Measurement Invariance of the German Version of the Revised Olweus Bullying Questionnaire - Leonie Dreißigacker; Sören Kliem (Psychological Test Adaptation and Development, 2023)
Abstract. The revised Olweus Bullying Questionnaire (OBQ-R) is a frequently used self-report measure that assesses bullying and victimization. This study evaluated the reliability and validity of the German OBQ-R with a representative sample of ninth graders (N = 12,444). Measurement invariance across gender and migration background was analyzed. The two-factor structure of the OBQ-R with high internal consistency reliability (victimization: ω = .89; bullying: ω = .89) was confirmed. Partial scalar invariance can be assumed for gender and migration background. The victimization subscale correlated in the predicted direction with depression (rs = .29), anxiety (rs = .30), and suicidal ideation (rs = .25). Additionally, the bullying subscale correlated in the expected directions with empathy (rs = −.18), problematic alcohol use (rs = .11), and problematic drug use (rs = .12). In summary, the German OBQ-R is a reliable and valid instrument for assessing bullying and victimization among adolescents in Germany.